Ultrasonic trapping and collection of airborne particulate matter enabled by multiple acoustic streaming vortices. (26th October 2021) - Su, Songfei; Chen, Jinyan; Liu, Pengzhan; Sun, Mengxin; Cheng, Huanbo
Abstract: The capability of trapping and collecting airborne particulate matter is of great applications in the fields of environmental engineering, healthcare systems, energy engineering, and so forth. In this work, we show a facile strategy of trapping and collecting airborne particulate matter by a simple and compact ultrasonic device system. In this device, a radiation plate is bonded with a Langevin transducer for generating circular standing flexural waves (CSFWs) in the plate. Under the excitation of the CSFWs in the radiation plate, an acoustic field and an acoustic streaming field can be induced in the air gap formed by the radiation plate and a sampling plate. Through numerical simulations, we find that the multiple acoustic streaming vortices symmetric about the central axis in the air gap are responsible for trapping and collecting airborne particulate matter onto the sampling plate, while acoustic radiation force contributes little. Also, it is numerically found and experimentally verified that the resonant acoustic field and the accompanying acoustic streaming field can be tuned by varying the thickness of air gap. Through experimentation, we investigate and clarify the dependency of collection performance on parameters such as the air gap thickness and radius, sonication time, driving voltage, and the angle between the radiation plate and the sampling plate. Due to its contactless and mild handling attributes, our ultrasonic airborne particulate matter sampler can circumvent the clogging and secondary pollution issues and ensure device reusability and little damage to samples compared with other airborne particulate matter processing methods.